2021
DOI: 10.3389/fcell.2021.634649
|View full text |Cite
|
Sign up to set email alerts
|

Superresolution Microscopy Reveals Distinct Phosphoinositide Subdomains Within the Cilia Transition Zone

Abstract: Primary cilia are evolutionary conserved microtubule-based organelles that protrude from the surface of most mammalian cells. Phosphoinositides (PI) are membrane-associated signaling lipids that regulate numerous cellular events via the recruitment of lipid-binding effectors. The temporal and spatial membrane distribution of phosphoinositides is regulated by phosphoinositide kinases and phosphatases. Recently phosphoinositide signaling and turnover has been observed at primary cilia. However, the precise local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 64 publications
(168 reference statements)
0
18
0
Order By: Relevance
“…Previous results have shown that INPP5E is concentrated at the cilia base, where it helps control phosphoinositide metabolism (43). Primary cilia are present on virtually all cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have shown that INPP5E is concentrated at the cilia base, where it helps control phosphoinositide metabolism (43). Primary cilia are present on virtually all cell types.…”
Section: Discussionmentioning
confidence: 99%
“…A loss of INPP5e activity reduced the oncogenic Shh signalling and proliferation of medulloblastoma cells (Conduit et al, 2017). PI(3,4,5)P 3 is enriched in a ring-like subdomain exclusive from that of PI(4,5)P 2 at the ciliary TZ (Conduit et al, 2021).…”
Section: Phosphoinositidesmentioning
confidence: 99%
“…A loss of INPP5e activity reduced the oncogenic Shh signalling and proliferation of medulloblastoma cells (Conduit et al, 2017). PI(3,4,5)P 3 is enriched in a ring‐like subdomain exclusive from that of PI(4,5)P 2 at the ciliary TZ (Conduit et al, 2021). The delivery of INPP5e through Arl13b restricts PI(3,4,5)P 3 levels in the cilia of projection neurons and regulates PI3K/Akt‐mediated neural development and differentiation (Humbert et al, 2012).…”
Section: Ciliary Lipids—composition and Local Modificationmentioning
confidence: 99%
“…As an inositol polyphosphate 5-phosphatase, INPP5E is mainly located in cilia in quiescent cells to maintain it is function and stability ( Conduit et al, 2021 ; Kosling et al, 2018 ). A portion of INPP5E is also located in the lysosome, and its membrane anchoring and enzymatic activity are necessary for autophagy ( Hasegawa et al, 2016 ; Sierra Potchanant et al, 2017 ).…”
Section: Cilia Associated Cellular Signallingmentioning
confidence: 99%